2014
DOI: 10.12659/msm.889758
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Esophageal Foreign Body Extraction Management: Flexible versus Rigid Endoscopy in 216 Adults of Beijing

Abstract: BackgroundThe aim of this study was to assess the effectiveness and complications of rigid endoscopy (RE) and flexible endoscopy (FE) for the extraction of esophageal foreign bodies (FB) in adults.Material/MethodsA retrospective analysis was conducted on the medical records of 216 adult patients with esophageal FB impaction treated at Peking University Third Hospital, Beijing, China, between January 2008 and December 2012.ResultsThe success rate of FB extraction was 100% (142/142) in patients treated with RE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 28 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, excluding the article by Wang. [ 48 ], there was no heterogeneity ( I 2 = 0.0%, τ 2 = 0.0%). This indicates that minor complications, such as mucosal edema and erosions, were not considered relevant in other studies.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, excluding the article by Wang. [ 48 ], there was no heterogeneity ( I 2 = 0.0%, τ 2 = 0.0%). This indicates that minor complications, such as mucosal edema and erosions, were not considered relevant in other studies.…”
Section: Discussionmentioning
confidence: 97%
“…A comparative study between flexible and rigid endoscopy has shown that the former has better results in terms of postoperative comfort and dysphagia (15% vs. 48%; p < 0.0001) [ 35 ]. The results in terms of successful rate of FB retrieval are similar between flexible endoscopy and rigid endoscopy, though the former carries a higher rate of minor complications, while the latter has a higher rate of perforation (0.0% vs. 3.2% p < 0.002) [ 36 , 37 ]. A meta-analysis comparing flexible versus rigid endoscopy for retrieval of upper esophageal FB showed that both were effective and safe, with similar success and overall complication rates ( p < 0.06) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Take China, for example, the most common type of FB is fish bones in south China and coastal provinces, in contrast with jujube pits in north China. 9,26 This may be explained by the following reasons. First of all, north China is the main place of origin of jujubes, while fish are daily diet in south China and coastal provinces with an abundant supply.…”
Section: Discussionmentioning
confidence: 99%
“…This makes RE widely used unnecessarily. 8,9 Furthermore, ingested FB could be classified into certain types according to their features, including food bolus, blunt objects, sharp-pointed objects, long objects, and special objects (ie, magnets, coins, and disk batteries). 2,3,7,[10][11][12] Most previous researches have studied them together, although the clinical characteristics and management differ greatly from each other.…”
Section: Introductionmentioning
confidence: 99%